Status of udder health performance indicators and implementation of on farm monitoring on German dairy cow farms: results from a large scale cross-sectional study - Böker, Andreas R.; Bartel, Alexander; Do Duc, Phuong; Hentzsch, Antonia; Reichmann, Frederike; Merle, Roswitha; Arndt, Heidi; Dachrodt, Linda; Woudstra, Svenja; Hoedemaker, Martina (Frontiers in Veterinary Science, 2023)
Regional benchmarking enables farmers to compare their animal health situation to that of other herds and identify areas with improvement potential. Therefore, the aim of this study was 1.) to describe the incidence of clinical mastitis (CM), 2.) to describe cell count based udder health indicators (annual mean test day average of the proportion of animals without indication of mastitis (aWIM), new infection risk during lactation (aNIR), and proportion of cows with low chance of cure (aLCC); heifer mastitis rate (HM)) and their seasonal variation, and 3.) to evaluate the level of implementation of selected measures of mastitis monitoring. Herds in three German regions (North: n = 253; East: n = 252, South: n = 260) with different production conditions were visited. Data on CM incidence and measures of mastitis monitoring were collected via a structured questionnaire-based interview. Additionally, dairy herd improvement (DHI) test day data from the 365 days preceding the interview were obtained. The median (Q0.1, Q0.9) farmer reported incidence of mild CM was 14.8% (3.5%, 30.8%) in North, 16.2% (1.9%, 50.4%) in East and 11.8% (0.0%, 30.7%) in South. For severe CM the reported incidence was 4.0% (0.0%, 12.2%), 2.0% (0.0%, 10.8%) and 2.6% (0.0%, 11.0%) for North, East and South, respectively. The median aWIM was 60.7% (53.4%, 68.1%), 59.0% (49.7%, 65.4%) and 60.2% (51.5%, 67.8%), whereas the median aNIR was 17.1% (13.6%, 21.6%), 19.9% (16.2%, 24.9%) and 18.3% (14.4%, 22.0%) in North, East, and South, respectively with large seasonal variations. Median aLCC was ≤ 1.1% (≤ 0.7%, ≤ 1.8%) in all regions and HM was 28.4% (19.7%, 37.2%), 35.7% (26.7%, 44.2%) and 23.5% (13.1%, 35.9%), in North, East and South, respectively. More than 90% of the farms participated in DHI testing and performed premilking routines. Several aspects of udder health monitoring, including exact documentation of CM cases, regular microbiological analysis of milk samples and the use of a veterinary herd health consultancy service were not applied on many farms. The results of this study can be used by dairy farmers and their advisors as benchmarks for the assessment of the udder health situation in their herds.